Rainfall patterns and its chemical characteristics in Singapore - Sam, Choy Ha. (2009)
A total of 41 wet precipitation samples were collected in Nanyang Technological University,from December 2008 to March 2009, which is also the Northeast monsoon season of Singapore. Each sample was analyzed by Ion Chromatography (IC) test for major anions (Cl−, NO3 −,SO42−, F-)and Inductively Coupled Plasma(ICP)test for major cations (Na+, K+, Ca2+ and Mg2+,Zn2+ and Fe2+).